Analysis of online learning based edmodo in pandemic era in atomic structure classes x at senior high school harapan 1 Medan - Hamidatun Nisa; Fathia Namira; Jasmidi Jasmidi; Ajat Sudrajat; Tita Juwitaningsih (Pascasarjana Universitas Negeri Medan, 2021)
Education in Indonesia since middle-March 2020 has undergone significant changes. Online learning to answer questions is a solution to the virus problem that has spread to cut cases of the Covid-19 virus using online media. Edmodo is a learning application that the application can use in bold type learning, including atomic structure material. This study analyzes the Edmodo-based understanding used for learning media on atomic structure material and how students respond to the Edmodo application in chemistry learning, especially atomic structure material. The research method used is descriptive qualitative. The results showed that the effectiveness of learning was 69%, application sustainability during the pandemic was 76%, ease of access was 97%, ease of communication was 61%, the clear assessment was 84%, and understanding of the material Edmodo was 59%. Implementing chemistry learning consists of (1) choosing Edmodo as a bold learning medium in chemistry learning based on analyzing student needs with reasoning and mastery of applications; (2) planning the application as a student learning medium as described in the Semester Learning Plan; (3) implementation in Edmodo-based online learning is carried out well and smoothly based on semester learning plan; and (4) edmodo as an application can help carry out chemistry learning in atomic structure subjects to measure student learning outcomes. So it can be concluded that Edmodo is a practical application to use during the Pandemic of Covid-19. Keywords: Covid-19 virus, edmodo, implementation of edmodo, online learning